Study of Auroral VLF Hiss Observed at Syowa Station, Antarctica - Tanaka, Yoshihito; Hayakawa, Masashi; Nishino, Masanori (1976)
P(論文) Observations of polarization, incident angle and arriving direction of auroral hiss were carried out at Syowa Station during the period of 1967 to 1970. The present paper consists of two parts. In Part I, we describe the equipment used for the measurement of polarization, incident and azimuthal angles and show the obtained results. The direction finding (DE) system used is based on the analysis of Lissajous' figures of electric and magnetic fields displayed on cathode ray tubes. The individual polarization of the received signal is also measured. Moreover, auroral hiss is decomposed into right-and left-handed polarized components, and these two components are continuously recorded. From the discussion of the observed results, it is found that auroral hiss has propagated downward in the azimuthal direction from a not so broad range around the magnetic meridian plane and its incident angle is also not so large. Additionally, in most cases, auroral hiss is known to consist of wave components downcoming from multiple directions in the azimuthal and incident planes. The DF system used was found to be effective in a few cases of isolated and sharp auroral hiss. However, this system should be re-examined because it is, strictly speaking, useful only for monochromatic waves, while the auroral hiss seems to have a noise-like nature. Therefore, a new DF system applying the correlation method is being planned to study, with more accuracy, the azimuthal and incident angles of noisy signals such as auroral hiss. The polarization of auroral hiss received on the ground seems to be almost right-handed circular, at VLF and LF, which is theoretically confirmed by the full wave calculation of the polarization using the realistic model of the auroral ionosphere. On the other hand, the observed polarization of ELF hiss is slightly right-handed circular, which can be reasonably accepted, taking into consideration the result of the full, wave calculation. In Part II, the morphological characteristics of auroral hiss are ...